Terroir and farming practices drive arbuscular mycorrhizal fungal communities in French vineyards - Battie-Laclau, Patricia; Taudière, Adrien; Bernard, Mathilde; Bodénan, Lucas; Duchemin, Myriam; de Roman, Yvan; Yol, Azimê; Barry-Etienne, Dominique (Frontiers in Microbiology, 2025)
BackgroundNature-based management of vineyards is at the heart of a sustainable development for the next decades. Although much is known about grapevine benefits from Arbuscular Mycorrhizal Fungi (AMF), little is known about the influence of vineyard terroir and farming practices on AMF communities.MethodsWe examined the relative effect of wine terroir and agricultural practices (organic, conversion, and conventional) on AMF abundance and diversity across 75 vineyards distributed over 14 wine terroirs in 6 winegrowing regions in France. We estimate AMF abundance by measuring spore density and root mycorrhization rates, and characterize AMF communities composition using metabarcoding by sampling both root and spore compartments for each vineyard.ResultsOrganic farming slightly increases AMF abundance (spore density and mycorrhization rate). Vineyards under conversion and using organic practices display a higher AMF diversity than conventional ones. Terroirs vary widely in terms of AMF abundance and diversity, with the median of OTUs count per sample ranging from 9 (Côte des Blancs) to 35 (Gigondas). The composition of AMF communities is structured mainly by terroir and in a lesser extent by practice. The effect of terroir on AMF communities is partially explained by distance decay and soil properties, but the majority of variation is still explained only by the terroir identity. Organic practices improve both abundance and diversity of AMF in vineyards, possibly leading to more productivity and resilience of grapevines.ConclusionThis large-scale study highlights the importance of terroir in our understanding of vineyard microbiome and paves the way to incorporation of AMF in microbial terroir studies and applications.